Installation of a family drip irrigation system for the improvement of the livelihood of small-scale farmers in comparison with surface irrigation - Khalifa, Ahmed; Ali, Mohamed; Sijali, I. V.; Yagoub, Adil; Eljali, Mohmed; Ali, Abdelgadir (Gezira Journal of Agricultural Science; Vol 12 No 2 (2014), 2014)
Drip irrigation is one of the most efficient methods of water use for crop production. Family drip systems are suitable for small land areas ranging from 10-2000 m 2 to irrigate horticultural crops. The system is a complete drip irrigation unit. It operates by gravity from a tank placed one meter high. It is a closed pipe-gravity system, and solid seasonal installation, for growing vegetables, flowers and other horticultural crops on flat or minor slope land. This experiment was established to evaluate a family drip system in comparison with surface irrigation for onion production under north Kassala conditions (Talkouk Locality). The results indicated that family drip system saved irrigation water by 67% and 59%, and increased the total yield of onion by 43% and 34% in sites one and two, respectively, as compared to local surface irrigation. The highest irrigation water productivity (2.98 and 2.73 kg/m 3 ) was obtained under family drip system and the lowest values were 1.25 and 1.28 kg/m 3 under surface irrigation in sites one and two, respectively. Moreover, the family drip system scored higher net return and benefit cost ratio compared to the surface irrigation system.         الري بالتنقيط هو أكثر الطرق كفاءة في استخدام المياه لإنتاج المحاصيل. نظام الري بالتنقيط العائلي هو نظام يناسب  المساحات الصغيرة التي تتراوح مساحتها بين 10 الي 2000  متر مربع, لري المحاصيل البستانية. النظام هو وحدة ري بالتنقيط  كاملة؛ يعمل بالجاذبية من خزان وضع علي ارتفاع 1 متر. هو نظام ذو انابيب مغلقة للجاذبية ويمكن تركيبة كل موسم بسهولة لزراعة الخضرواتِ والزهور والمحاصيل البستانية الأخرى على الأراضِي المنحدرة والمستويةِ أَو البسيطةِ. تأسست هذه التجربة لتقييم نظام الري بالتنقيط العائلي مقارنة مع الري السطحي المحلي لإنتاج البصل تحت ظروف شمال كسلا محلية تلكوك. اشارت النتائج إلى أن نظام الري بالتنقيط العائلي حفظ مياه الري بنسبة 67٪ و 59٪، وزيادة الانتاجية بنسبة 43٪ و 34٪ في الموقع الاول والثاني على التوالي مقارنة مع الري السطحي المحلي. ايضا تم الحصول على أعلى إنتاجية لمياه الري (2.98 و2.73 كيلوجرام متر مكعب) تحت نظام الري بالتنقيط العائلي وكانت أقل القيم   (1.25 و 1.28 كيلوجرام متر مكعب) تحت الري السطحي في الموقعين الاول والثاني. علاوة على ذلك، سجل نظام الري بالتنقيط العائلي اعلي عائد ومنفعة مقارنة لنظام الري السطحي.